ANALYSIS OF THE RELATIONSHIP OF GREEN FINANCE TO THE INDONESIAN ECONOMY - Luciana kartini Simanjuntak; Salmayani; Dina Rahayu; Indri Gemi Nestiti; Muammar Khaddafi (Universitas Efarina, 2023)
Green financecurrently very influential on any activity related to financial or economic activities throughout the world. One of the big challenges faced is global warming which can hamper supply chains or company assets due to climate change. Climate change and environmental damage are closely related to the economy. Moreover, as the environment worsens, green financebe good environmental protection at this time to make investment and financing decisions as well as potential profits. This research concludes that there is a link between green finance and the economy, creating positive dynamics that promote sustainable growth, economic diversification and environmental risk mitigation. Green finance not only opens the door to new investment and innovation, but also helps shape a more environmentally friendly and resilient economy.